A History of Developmental and Behavioral Pediatrics at the University of Rochester : 1947-2019 - Davidson, Philip William, 1941-2022; Hyman, Susan L. (Book collections on Project MUSE., 2021)
A history of the University of Rochester Medical Center's Developmental and Behavioral Pediatrics Division from its inception in 1947 through 2019.